Edukasi Pendidikan Anti Korupsi Sebagai Upaya Menciptakan Generasi Anti Korupsi - M. Rizkal Fajri; Pelita Aulia; Shinta Bella Puspita; Dio Widiyatma; Ratu Desma Alya Rohali; Adi Saputra Supriyono (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
This community service program aims to raise awareness and understanding of anti-corruption values among elementary school students through interactive education. The activities were carried out in August, involving students, teachers, and parents as the target community. The method used was Participatory Action Research (PAR), with stages including observation, focus group discussions (FGD), teacher training, and program evaluation. The results showed a significant increase in students' understanding of honesty and integrity values. Additionally, the program successfully initiated a new institution, the "Honesty Group," which acts as a supervisor of honesty within the school. This program provides tangible contributions to shaping young generations committed to anti-corruption values from an early age.